Estimating amplitudes of internal waves using satellite ocean colour imagery of the South China Sea - Su, F.-C.; Ho, C.-R.; Zheng, Q.; Kuo, N.-J. (International journal of remote sensing, 2008)
A method is presented for estimating the amplitudes of internal waves (IWs) in ocean colour imagery. The method is tested in the northern South China Sea (SCS) because the environmental conditions there are such that IWs are generated frequently and can therefore be observed easily. A relationship between satellite-derived chlorophyll concentration (chl) and the amplitudes of IWs is obtained. Using a deep chlorophyll maximum (DCM) model, the amplitude at the light penetration depth can be estimated. From theoretical models, the amplitude of an IW at the depth where the maximum vertical isopycnal displacement appears is also derived. The results indicate that the amplitudes of IWs in the northern SCS determined by the methods developed in this study are comparable with historical regional data.